2017
DOI: 10.2196/preprints.9416
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Technology-Based Peer Support Intervention Program for Preventing Postnatal Depression: Protocol for a Randomized Controlled Trial (Preprint)

Abstract: Background: Multiple international agencies, including the World Health Organization (WHO)

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…These findings are consistent with the mixed nature of research on peer support in the perinatal period. When well-trained, resourced and supervised, peer supporters can be an accessible and effective workforce [ 18 ], but fail to effectively support mothers without these forms of oversight in place [ 16 , 17 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with the mixed nature of research on peer support in the perinatal period. When well-trained, resourced and supervised, peer supporters can be an accessible and effective workforce [ 18 ], but fail to effectively support mothers without these forms of oversight in place [ 16 , 17 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, however, the evidence-base on where peer supporters may most effectively fit within perinatal mental health service delivery remains unclear. Most of the research on peer support during the perinatal period has focussed on evaluating specific, formal interventions provided directly by peers, and the efficacy of these interventions has been mixed [ 16 20 ]. In contrast, there has been little research examining the other adjunctive or informal functions of peer support which are often widely available through charities, non-profit and non-governmental organisations, despite the fact that a recent review outside the perinatal period has found that these latter functions may offer greater clinical benefit [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Peer group-based technology applications have been developed just like virtual peer support for family can improve wellbeing of their family that have a chronic illness (22). One of them is the implementation of a peer support intervention program which is able to reduce the risk of postnatal depression (23). The use of peer group-based text massage can use short messages with an online approach where the results are that the use of online peer groups is more efficient (24).…”
Section: Discussionmentioning
confidence: 99%
“…Peer group-based technology applications have been developed just like virtual peer support for family can improve wellbeing of their family that have a chronic illness (Jeffrey et al, 2020). One of them is the implementation of a peer support intervention program which is able to reduce the risk of postnatal depression (Shorey et al, 2018). The use of peer group-based text massage can use short messages with an online approach where the results are that the use of online peer groups is more efficient (Swendeman et al, 2019).…”
Section: Discussionmentioning
confidence: 99%